Measurement Of Shariah Stock Performance Using Risk Adjusted Performance - Zuhairan Y Yunan; Mia Rahmasari (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2015)
The aim of this research is to analyze the shariah stock performance using risk adjusted performance method. There are three parameters to measure the stock performance i.e. Sharpe, Treynor, and Jensen. This performance’s measurements calculate the return and risk factor from shariah stocks. The data that used on this research is using the data of stocks at Jakarta Islamic Index. Sampling method that used on this paper is purposive sampling. This research is using ten companies as a sample. The result shows that from three parameters, the stock that have a best performance are AALI, ANTM, ASII, CPIN, INDF, KLBF, LSIP, and UNTR.DOI: 10.15408/aiq.v7i1.1364